Trademarking activities and total factor productivity: some evidence for British commercial banks using a metafrontier approach - Duygun, Meryem; Sena, Vania; Shaban, Mohamed (Elsevier, 2016)
In this paper, we compute a non-parametric Metafrontier Malmquist index to evaluate the Total Factor Productivity (TFP) change among UK-based trademarking and non-trademarking commercial banks between 2005 and 2013. The use of the metafrontier approach allows us to: a) identify the drivers of TFP growth for each group of banks, b) compare the TFP growth of each group to the TFP growth experienced by the whole industry, and c) assess the extent to which the former catches up with the latter measured along the metafrontier. Our results suggest that TFP has been increasing among trademarking banks up to the onset of the financial crisis but this process has since reversed. The catch-up indexes suggest that both groups of banks were catching up with the metafrontier up to the financial crisis although the drivers of this process differed between the two groups. After the financial crisis, improvements in technology have been driven by a small number of commercial banks i.e. the non- trademarking banks. These results suggest that a large section of the commercial banking sector has not been able to overcome the effects of the financial crisis.